The use of everolimus in renal-transplant patients - Pascual, Julio (Dove Medical Press, 2009)
Despite advances in immunosuppressive therapy, long-term renal-transplantation outcomes have not significantly improved over the last decade. The nephrotoxicity of calcineurin inhibitors (CNIs) is an important cause of chronic allograft nephropathy (CAN), the major driver of long-term graft loss. Everolimus is a proliferation signal inhibitor with a mechanism of action that is distinct from CNIs. The efficacy and tolerability of everolimus in renal-transplant recipients have been established in a wide range of clinical trials. Importantly, synergism between everolimus and the CNI cyclosporine (CsA) permits CsA dose reduction, enabling nephrotoxicity to be minimized without compromising efficacy. Currently, everolimus is being investigated in regimens where reduced exposure CNIs are used from the initial post-transplant period to improve renal function and prevent CAN. By inhibiting the proliferation of smooth muscle cells, everolimus may itself delay the progression or development of CAN. Although everolimus is associated with specific side effects, these can generally be managed. By targeting the main causes of short- and long-term graft loss, everolimus has a key role to play in renal transplantation, which is being explored further in a number of ongoing Phase III–IV trials.